Opinion formation in social networks with strong neighborhood influences - Lian, Zi Yun (Nanyang Technological University, 2020)
As technology is continuously evolving, the web has become an essential part of our lives. We make use of the web for e-commerce, networking, entertainment, to obtain news and information, and many more. Also, opinions form an important aspect in our everyday lives as we decide on minor to major issues. Therefore, there is a need to research on how individuals form bonds, communicate and influence one another’s opinions where information and communication could be obtained and done easily online today. This project investigates opinion formation in social networks and how they evolve, especially due to strong neighborhood influences. To do so, popular network and opinion models (Barabási–Albert network model and Deffuant-Weisbuch opinion formation model with rewiring extension) that resemble real-life networks best, are adopted for simulations. In the simulations of social networks, individuals are represented as nodes and the relationships between one another are represented as edges. In reality, individuals could be connected on several layers, where they agree or disagree on more than one issue. Hence, the simulations were done in the context of having double-layers. Simulations focused heavily on rewiring rates, especially according to the friend-of-friend theory, which is reflected in reality, as we introduce our mutual friends to one another to widen our social circle. However, more work has to be done to further develop the codes used in this project, and to include many other factors that were either not considered, or set to constant, to ensure that the topic will be well and thoroughly investigated.